Comparison of Efficacy of Oral Lacosamide Versus Oral Topiramate in Young Adults with Chronic Migraine - Butt, Nabeel Tahir; Usman, Muhammad; Bhatti, Abdul Hameed; Ahsan, Farah; Azam, Rizwan; Kazmi, Kashif Raza (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the efficacy of the new anti-epileptic drug Lacosamide vs conventional treatment with Topiramate for the treatment of young adults presenting with chronic migraine. Study Design: Randomized controlled trial. Place and Duration of Study: Department of Anesthesia (Pain clinic) and Department of Medicine, Combined Military Hospital Rahim Yar Khan, Pakistan from Jan to Jun 2023. Methodology: The patients were divided into two groups, Group-T (n=145) and Group-L (n=145). Patients in Group-T received oral Topiramate at a dose of 50 mg twice a day while Group-L received oral Lacosamide at a dose of 100 mg twice a day. All the participants received the drug regime in both groups for a period of three months. Primary variables observed were improvement in the quality of life and migraine free days during therapy due to the disease according to the MIDAS (Migraine disability assessment) scoring system before and after 90 days of treatment. Results: While observing the primary variables, median MIDAS (Migraine Disability Assessment) scores before therapy were 11.00 (IQR=2.00) in Group-L versus 11.00 (IQR=3.00) in Group-T (p=0.743). The same median scores were 6.00 (IQR=1.00) in Group-L versus 8.00 (IQR=0.00) in Group-T (p<0.001). Mean days to an episode of migraine before start of therapy were 17.17±2.04 days in Group-L versus 17.06±1.99 days in Group-T (p=0.663). During therapy for 90 days, migraine free days following up to an episode of migraine were.. Conclusion: Treatment with oral Lacosamide resulted increased migraine free days with a more conducive adverse effect profile.